2000
DOI: 10.1046/j.1365-2249.2000.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, tumour necrosis factor-alpha (TNF-α) and atherosclerosis

Abstract: SUMMARYAgeing is associated with increased inflammatory activity in the blood. The purpose of this study was to investigate if age-related increased plasma levels of TNF-a were associated with atherosclerosis in a cohort of 130 humans aged 81 years. The elderly cohort had increased circulating levels of TNF-a , Creactive protein (CRP), total cholesterol (TC), low-density lipoproteins (LDL) and a low high-density lipoprotein (HDL)/TC ratio compared with a young control group (n 44). The elderly cohort was divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
206
2
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(226 citation statements)
references
References 48 publications
(59 reference statements)
13
206
2
5
Order By: Relevance
“…As expected, advanced age and menopausal status were associated with elevated CRP levels. 39,40 Iannuzzi et al found that higher hs-CRP levels were associated with obstructive sleep apnea, and the effects were mediated by being overweight and obese. 41 Similarly, decreasing body mass index by lifestyle interventions such as exercise and dietary restrictions was shown to decrease hs-CRP levels in a randomized study of 439 postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, advanced age and menopausal status were associated with elevated CRP levels. 39,40 Iannuzzi et al found that higher hs-CRP levels were associated with obstructive sleep apnea, and the effects were mediated by being overweight and obese. 41 Similarly, decreasing body mass index by lifestyle interventions such as exercise and dietary restrictions was shown to decrease hs-CRP levels in a randomized study of 439 postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma levels of TNF-α were associated with the pathogenesis of diabetes and atherosclerosis (21). TNF-α was related to endothelial dysfunction in patients with type 2 diabetes mellitus after myocardial infarction (6) and actively involved in the progression of atherosclerosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…A ging is associated with increased inflammatory activity (1,2). Serum Creactive protein (CRP) is a sensitive marker of systemic low-grade inflammation and is an important predictor of type 2 diabetes (3,4) and cardiovascular disease (CVD) (5).…”
mentioning
confidence: 99%